The Acts of Paul a new translation with introduction and commentary - Pervo, Richard I. (Havertown : James Clarke & Co, 2014)
A new translation of the Acts of Paul with introduction and commentary.
Print version record.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Acts of Paul -- Translations; Acts of Paul -- Commentaries; Acts of Paul -- Criticism, interpretation, etc; Acts of Paul; RELIGION -- Biblical Studies -- Jesus, the Gospels & Acts; RELIGION -- Biblical Studies -- New Testament; RELIGION / Biblical Studies / Paul's Letters; Electronic books; Commentaries; Criticism, interpretation, etc; Translations